GAMBARAN TINGKAT KECEMASAN DAN DERAJAT SERANGAN ASMA PADA PENDERITA DEWASA ASMA BRONKIAL (Studi di WilayahKerja Puskesmas Gunungpati, Kota Semarang Tahun 2016) - Yusnik Adi Putra; Ari Udiyono; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Bronchial asthma is a chronic inflammatory disease infected respiratory tract caused by the onset of someone airway due to a stimulation from extrinsic factor such as allergic or intrinsic factor such as anxiety. This study aims to know anxiety level overview and the degree of asthma attack in bronchial asthma patient at Health Center of Gunungpati working area. This study was a descriptive observational study with cross sectional study design. The sample of this study were 48 bronchial asthma patients. Descriptive analyisis showed that bronchial asthma patient who experienced more anxiety (79,2%) compared to patient who did not experience anxiety (20,8%). The level of anxiety experienced by most is severe anxiety (55,3%) occured on women (52,4%), aged 46-65 years (61,9%), with revenues ≤UMR (85,7%), did not work (52,4%), last in elementary education (52,4%). The level of asthma attack degree by most is moderate asthma attack (54,2%), occured on women (69,2%), aged 46-65 years (53,8%), with revenues ≤UMR (76,9%), did not work (50,0%), last in elementary education (50,0%). Asthma patient who experienced mild asthma attack, moderate nor severe by most experienced severe anxiety. Conclused that most bronchial asthma patient experienced moderate asthma attack with severe level of anxiety before attack occured. It is advisable to people with asthma and their families to frequently follow counseling to health workers in order to apply efforts and a healthy lifestyle to prevent the onset of anxiety in asthma sufferers who can trigger asthma attacks.